PELUANG DAN TANTANGAN INOVASI PRODUK ASURANSI UMUM SYARIAH - Ichsan, Nurul (Ekonomi Islam, 2016)
Takaful already known in the State Indonesia Takaful Company since its establishment in 1994 to meet  the  demand  for  insurance  services  is  increasingly  perceived  either  by  individuals  or businesses in Indonesia. Insurance is a financial means in the order of domestic life, both in the face of the fundamental risks or face the risk of property owned. This paper attempts to read and look at the opportunities and challenges of the factors Takaful is an external assessment of the condition of Takaful current and future picture that will affect the process of achieving the financial objectives of an institution of sharia. By reviewing and reading the situation will get the characteristics of strength and weakness analysis of Takaful is based on the strength of internal and external environments. This paper also discusses the opportunities and challenges of Islamic commercial insurance product innovation to appear innovative products and services that completely excavated from the basic concept of sharia and also illustrates some of the things that cause relatively low penetration of Islamic insurance market at the moment.